An Investigation Into Cross-border Mergers and Acquisitions Effect on Shareholders Wealth. Evidences of The UK and The US Acquiring Firms from 2002 to 2012 - Nguyen, Hong Nhung (2012)
Since the past few decades, the international mergers and acquisitions have accelerated and become an important strategy for any corporation and its waves are expected to continue. Thus, it is important to know whether shareholders of acquiring companies could experience gains from the mergers. Objective of this study is to provide readers an overview of cross borer mergers and acquisitions. By investigating a sample of 257 international mega deals made by US and UK bidders over the period 2002-2012, the aim is to examine the impact of mergers and acquisitions on bidder shareholder’s returns. Furthermore, factors that influence the returns are also examined. This paper shows that, on average, cross border M&A create a statistically significant abnormal returns of 0.12% for the US bidders during eleven-day event window, while the gains are not clear for UK bidders. There is evidence that relative size of target to acquirer and economic condition of target country affect the bidder shareholder returns.